Molding composition comprising black colorant
By using UV-resistant laser transparent plastic materials with specific black colorants, the problems of existing materials discoloration and poor laser mark printing when UV exposure are solved, and higher UV resistance and laser printing are achieved.
Patent Information
- Application Number
- CN202380054800.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-11
- Publication Date
- 2025-03-07
AI Technical Summary
Existing black laser transparent plastic materials discolor when UV is exposed and have insufficient UV resistance, and are also poor in printing during laser marking.
Anti-UV laser transparent plastic material containing a specific black colorant is used, which consists of polyamide and polyester and has an initial laser transmittance of at least 20% at 1064 nm.
The material's UV resistance and laser printing properties are improved, allowing it to maintain its color stability under UV exposure conditions and exhibit better printing results during laser marking.
Smart Images

Figure BDA0005248885880000101 
Figure BDA0005248885880000241 
Figure BDA0005248885880000281
Abstract
Description
Technical Field
[0001] The invention relates to a molding composition comprising a black colorant, a plastic article produced therefrom and the use of the molding composition in laser welding. Background Art
[0002] Due to the classic appearance of the manufactured products, black plastic materials are very popular in many fields, especially in automotive parts, household appliances, electronic products, etc. In certain manufacturing processes of plastic products, black plastic materials are required to have special optical properties, such as transparency in laser welding processes.
[0003] Laser welding (as a tool for joining plastic parts) may become a universal method. A prerequisite for using laser welding is that the radiation emitted by a laser, typically in the wavelength range of 780 to 1200 nm, first penetrates a part made of a plastic material that has sufficient transparency to the laser of the wavelength used (i.e., a laser transparent part), and is then absorbed in a thin layer by a second part made of a laser absorbing plastic material below the laser transparent part (i.e., a laser absorbing part). Within the thin layer that absorbs the laser light, the laser energy is converted into heat, and this causes melting within the contact area and ultimately results in a weld that bonds the laser transparent part to the laser absorbing part. Carbon black is most commonly used in plastic materials to provide laser absorbing plastic materials because it can provide huge economic benefits. For this reason, a laser transparent material that is also black is usually used to provide a uniform color between the laser absorbing part and the laser transparent part. Various laser transparent colorants can be used to provide a black color in the laser transparent material, for example, black colorants such as nigrosine, naphthalocyanine, nigrosine, phthalocyanine, porphyrin, pyrene, quaternaryl triphenylene, azo dyes, anthraquinones, pyrazolones, squarylium derivatives, and imine dyes; or mixtures of colored colorants, such as a mixture of red and green colorants to simulate a black colorant.
[0004] Laser transparent plastic materials based on common polymers such as polyamide and polyester have been proposed. For example, WO2019216368A1 describes a resin composition with high light transmittance that can provide a molded article with excellent laser weldability to an absorbing resin member. The resin composition includes a polyamide resin, a maleic anhydride-modified polyphenylene ether resin, a phosphazene flame retardant, a zinc metal oxide, and an optically transparent dye. WO 2011154518A1 describes a laser transparent PBT composition containing organic additives, to which inorganic and organic pigments and dyes such as nigrosine and anthraquinone can be added as colorants.
[0005] Parts or articles made from those black laser transparent plastic materials can exhibit good laser transparency, but they are found to be insufficiently resistant to ultraviolet (UV) rays and suffer from high discoloration upon UV exposure. As the applications of parts or articles made therefrom expand to exposure to sunlight, the demand for UV laser transparent plastic materials is increasing.
[0006] The inventors have found that the UV resistance of laser transparent plastic materials cannot be effectively improved by conventional UV absorbers and / or UV stabilizers. UV absorbers and / or UV stabilizers can protect polymers or resins from discoloration, but cannot prevent UV-induced discoloration of laser transparent colorants such as those contained in the plastic material.
[0007] The inventors have also found that conventional laser transparent plastic materials containing laser transparent colorants generally exhibit unsatisfactory printability when laser marking is applied. Laser marking has increased importance in different fields as a tool for marking products, especially plastic products, because it is a non-contact, fast and flexible marking method, while providing durable and wear-resistant writing. The laser useful for the laser marking method can be in the wavelength range of 150nm to 2000nm, such as 150nm to 380nm (i.e., UV laser marking). In such a method, a laser beam is irradiated on the article to be marked, and the laser energy is converted into heat, which causes a change in color and a transformation of the molecular structure or destruction (cutting) of the material to produce a visible mark in the form of a desired pattern or image. By laser marking, a mark can be produced on or below the surface of the article.
[0008] Therefore, there is a need to provide a black laser transparent plastic material having desirable UV resistance while exhibiting excellent laser transparency. It would be further desirable if a black laser transparent plastic material could exhibit improved laser marking performance (ie, printability). Summary of the invention
[0009] The inventors have surprisingly found that UV resistant laser transparent plastic materials based on polyamide and polyester can be provided by using a specific black colorant. It has also been found that laser transparent plastic materials comprising a specific black colorant can exhibit improved laser printability.
[0010] Therefore, in a first aspect, the present invention provides a molding composition comprising
[0011] (A) 20% to 98% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0012] (B) 0.01 to 0.5% by weight of a black colorant,
[0013] (C) 0% to 50% by weight of a reinforcing agent, and
[0014] (D) 0% to 50% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0015] (E) 0% to 10% by weight of one or more additives,
[0016] each based on the total weight of the molding composition,
[0017] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0018] In a second aspect, the present invention provides the use of a molding composition as described herein for producing a laser transparent plastic part or article.
[0019] In a third aspect, the present invention provides an article produced using a molding composition as described herein, such as a housing for an automotive radar or an automotive camera. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Laser marking images on samples C1 to C3, E1 and E2 are shown. DETAILED DESCRIPTION
[0021] The present invention will be described in detail hereinafter. It should be understood that the present invention can be implemented in many different ways and should not be construed as limited to the embodiments set forth herein.
[0022] The singular forms "a / an," and "the" include plural referents unless the context clearly dictates otherwise. The terms "comprise," "comprising," and the like are used interchangeably with "contain," "containing," and the like and are to be interpreted in a non-limiting, open-ended manner. That is, for example, additional components or elements may be present. The expression "consists of," "consisting of," or cognates thereof, may be included in "comprises," "comprising," or cognates thereof.
[0023] As used herein, the term "initial laser transmittance" is intended to refer to the laser transmittance measured on a freshly prepared molded sample under moisture protection, for example, within 72 hours, preferably within 24 hours after its preparation.
[0024] As used herein, the term "crystalline polymer material" is intended to refer to a polymer material having crystalline domains between macromolecular chains, as evidenced by the presence of one or more distinct endothermic peaks in a melting point measurement by differential scanning calorimetry (DSC). The melting enthalpy is expressed relative to the weight of the polymer. Herein, a "distinct" endothermic peak refers to a peak having a melting enthalpy of at least 5 J / g.
[0025] The term "amorphous polymer material" as used herein is intended to be a polymer material having no or substantially no crystalline domains between macromolecular chains, as evidenced by the absence of an endothermic peak or by the presence of an endothermic peak with a melting enthalpy of less than 5 J / g in melting point measurement by differential scanning calorimetry (DSC).
[0026] <Molding composition>
[0027] As described above, the present invention provides a molding composition comprising
[0028] (A) 20% to 98% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0029] (B) 0.01 to 0.5% by weight of a black colorant,
[0030] (C) 0% to 50% by weight of a reinforcing agent, and
[0031] (D) 0% to 50% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0032] (E) 0% to 10% by weight of one or more additives,
[0033] each based on the total weight of the molding composition,
[0034] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0035] Component (A)
[0036] The molding composition according to the present invention comprises as component (A) a crystalline polymer material, which is at least one selected from the group consisting of polyamide, polyester, a blend containing polyamide, and a blend containing polyester.
[0037] Polyamide
[0038] Useful polyamides may be those derived from at least one monomer selected from the group consisting of lactams, amino acids, a combination of dicarboxylic acids and diamines, and a combination of dicarboxylic acid chlorides and diamines.
[0039] For example, useful polyamides may be those derived from lactams having 4 to 30 carbon atoms or amino acids having 4 to 30 carbon atoms.
[0040] Suitable lactams preferably have 6 to 18 carbon atoms, more preferably 6 to 12 carbon atoms. Examples of lactams may include, but are not limited to, caprolactam, enantholactam, caprylolactam, caprinolactam, undecanolactam, laurolactam, or any combination thereof.
[0041] Suitable amino acids preferably have 6 to 18 carbon atoms, more preferably 6 to 12 carbon atoms. Examples of amino acids may include, but are not limited to, 2-aminoadipic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, or any combination thereof.
[0042] Examples of useful polyamides are also those derived from a combination of a dicarboxylic acid having 6 to 32 carbon atoms and a diamine having 4 to 24 carbon atoms or a combination of a dicarboxylic acid chloride having 6 to 32 carbon atoms and a diamine having 4 to 24 carbon atoms.
[0043] Suitable aliphatic diamines preferably have 4 to 24 carbon atoms, more preferably 4 to 18 carbon atoms, such as 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14 carbon atoms. The aliphatic diamine can be a linear or branched aliphatic diamine. Examples of aliphatic diamines can include, but are not limited to, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine. , 1,20-eicosanediamine, 1,22-eicosanediamine, 2-methylpentane-1,5-diamine, 3-methylpentane-1,5-diamine, 2,5-dimethylhexane-1,6-diamine, 2,4-dimethylhexane-1,6-diamine, 3,3-dimethylhexane-1,6-diamine, 2,2-dimethylhexane-1,6-diamine, 2,2,4-trimethylhexane-1,6-diamine , 2,4,4-trimethylhexane-1,6-diamine, 2,3-dimethylheptane-1,7-diamine, 2,4-dimethylheptane-1,7-diamine, 2,5-dimethylheptane-1,7-diamine, 2,2-dimethylheptane-1,7-diamine, 2-methyloctane-1,8-diamine, 1,3-dimethyloctane-1,8-diamine, 1,4-dimethyloctane-1,8-diamine, 2, 4-dimethyloctane-1,8-diamine, 3,4-dimethyloctane-1,8-diamine, 4,5-dimethyloctane-1,8-diamine, 2,2-dimethyloctane-1,8-diamine, 3,3-dimethyloctane-1,8-diamine, 4,4-dimethyloctane-1,8-diamine, 2,4-diethylhexane-1,6-diamine, 5-methylnonane-1,9-diamine, and any combination thereof.
[0044] Suitable dicarboxylic acids may be aliphatic or aromatic and preferably have 4 to 22 carbon atoms, such as 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms. Examples of dicarboxylic acids may include, but are not limited to, adipic acid, pimelic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, terephthalic acid, isophthalic acid, and any combination thereof.
[0045] Suitable dicarboxylic acid chlorides may be aliphatic or aromatic and preferably have 4 to 22 carbon atoms, such as 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms. Examples of dicarboxylic acid chlorides may include, but are not limited to, adipoyl chloride, pimeloyl chloride, azelayl chloride, sebacoyl chloride, undecanedioyl chloride, and any combination thereof.
[0046] For example, the polyamide as component (A) may be at least one selected from the group consisting of PA6, PA7, PA8, PA9, PA11, PA12, PA410, PA510, PA513, PA515, PA66, PA69, PA610, PA612, PA613, PA614, PA618, PA636, PA88, PA810, PA812, PA1010, PA1012, PA1014, PA1018, PA1210, PA1212, PA1214, PA1218, PA1313, PA1410, PA1412, PA1414, PA1418, PA4T, PA9T, PA10T, PA11T, or any combination thereof, preferably PA6 or PA66.
[0047] Useful polyamides preferably have a weight average molecular weight (Mw) of at least 6,000, more preferably at least 10,000, still more preferably 15,000 or more, further preferably 20,000 or more, as measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) is preferably not more than 35,000, more preferably not more than 30,000, even more preferably not more than 26,000. Alternatively or additionally, useful polyamides may have a relative viscosity in the range of 1.8 to 4.0 as measured in 96% by weight sulfuric acid at 25°C.
[0048] In some embodiments according to the present invention, the molding composition according to the present invention comprises a polyamide selected from PA6, PA66 or any combination thereof, preferably PA 66 as component (A).
[0049] Polyamide-containing blends
[0050] Suitable polyamide-containing blends may be any blend comprising a polyamide as described above, including not only blends of different polyamides but also blends of polyamides with polymers other than polyamides. Blends of different polyamides are particularly useful as polyamide-containing blends.
[0051] Polyester
[0052] Useful polyesters may be those derived from aromatic dicarboxylic acids and aliphatic or aromatic dihydroxy compounds. Polyesters of this type are known per se and contain aromatic rings derived from aromatic dicarboxylic acids and which are optionally substituted, for example, by halogens such as chlorine or bromine, or by C1-C4-alkyl groups such as methyl, ethyl, isopropyl or n-propyl, or n-butyl, isobutyl or tert-butyl.
[0053] Suitable aromatic dicarboxylic acids are, for example, 2,6-naphthalenedicarboxylic acid, terephthalic acid and isophthalic acid or combinations thereof.
[0054] For example, useful polyesters may be polyalkylene terephthalates, particularly those derived from aliphatic dihydroxy compounds having 2 to 10 carbon atoms. Preferred aliphatic dihydroxy compounds are diols having 2 to 6 carbon atoms, such as 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol and neopentyl glycol, or any combination thereof.
[0055] Examples of preferred polyesters are polyalkylene terephthalates derived from alkanediols having 2 to 6 carbon atoms, particularly polyethylene terephthalate (PET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), and any combination thereof, with PBT being most preferred.
[0056] In some embodiments, the molding composition according to the present invention comprises polybutylene terephthalate. The polybutylene terephthalate may be a homopolyester obtained by esterification of 1,4-butanediol with terephthalic acid or by transesterification with an ester of terephthalic acid.
[0057] Alternatively, the polybutylene terephthalate may be a copolyester derived from 1,4-butanediol, terephthalic acid or its ester and no more than 30 mol% of at least one other monomer selected from diols, dicarboxylic acids or a combination thereof. There is no limitation on the type of copolyester, including, for example, block copolymers, random copolymers, graft copolymers and alternating copolymers.
[0058] The polybutylene terephthalate preferably contains not more than 20 mol %, preferably not more than 10 mol %, more preferably not more than 5 mol % of units derived from at least one other monomer, based on the total monomers constituting the polybutylene terephthalate.
[0059] Examples of other monomers may be aliphatic dicarboxylic acids having up to 20 carbon atoms, alicyclic dicarboxylic acids having 7 to 12 carbon atoms, aromatic dicarboxylic acids having 8 to 16 carbon atoms, or any combination thereof, preferably selected from the group consisting of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanoic acid, hexadecanedioic acid, dimer acid, isophthalic acid, Phthalic acid, 2,6-naphthalene dicarboxylic acid, hexahydrophthalic acid, hexahydroisophthalic acid, hexahydroterephthalic acid, 1,2-cyclopentane dicarboxylic acid, 1,3-cyclopentane dicarboxylic acid, humic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-diphenylmethane dicarboxylic acid, 4,4'-diphenyl ketone dicarboxylic acid and any combination thereof, more preferably succinic acid, glutaric acid, adipic acid, pimelic acid, isophthalic acid, phthalic acid or any combination thereof.
[0060] Examples of other monomers may be aliphatic diols having 2 to 12 carbon atoms, alicyclic diols having 6 to 12 carbon atoms, 2-4 The polyoxyalkylene glycol of oxyalkylene units, aromatic glycols having 6 to 14 carbon atoms, or any combination thereof, is preferably selected from the group consisting of 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,6-hexanediol, neopentyl glycol, 1,3-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, ditetramethylene glycol, decanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, bis-1,4-(hydroxymethyl)cyclohexane, diethylene glycol, polytetramethylene glycol, bisphenol, xylylene glycol, naphthalene diol, and any combination thereof, more preferably ethylene glycol, diethylene glycol, or a combination thereof.
[0061] Useful polybutylene terephthalates preferably have a viscosity in the range of 90 to 170 ml / g, preferably 100 to 135 ml / g, more preferably 100 to 120 ml / g as measured in 0.005 g / ml phenol / 1,2-dichlorobenzene solution (1:1 mass ratio) according to ISO 1628-5. Alternatively or additionally, useful polybutylene terephthalates may have a weight average molecular weight (Mw) of 60,000 to 100,000 as measured by gel permeation chromatography (GPC).
[0062] Polyester blends
[0063] Suitable polyester-containing blends can be any blends comprising polyesters as described above, including not only blends of different polyesters, but also blends of polyesters with polymers other than polyesters. Blends of polyesters with polymers other than polyesters are particularly useful as polyester-containing blends.
[0064] The polymer material may be present in the molding composition according to the invention in an amount of 20 to 98% by weight, preferably 30 to 80% by weight, more preferably 35 to 75% by weight, for example 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75% by weight, based on the total weight of the molding composition.
[0065] It should be understood that when referred to herein, the amount of polymeric material as component (A) is intended to refer to one or more corresponding polymers themselves. Commercially available polymeric materials usually have some (certain) additives intentionally added to provide one or more desired properties, such as color, strength, stability, etc., which additives will not be counted in the amount of polymeric material.
[0066] Component (B)
[0067] The molding composition according to the present invention contains a black colorant as component (B), which is laser transparent and allows the molding composition according to the present invention to have an initial laser transmittance at 1064 nm of at least 20%, and a ratio of the initial laser transmittance at 780 nm to the initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0068] Preferably, the molding composition according to the invention has an initial laser transmittance at 1064 nm of at least 20% and a ratio of the initial laser transmittance at 780 nm to the initial laser transmittance at 1064 nm in a range of less than 10%, or even less than 5%.
[0069] The laser transmittance of the molding compositions as specified herein is determined according to thermoelectric power measurements or UV-visible spectrophotometric measurements, preferably UV-visible spectrophotometric measurements, as described in the examples hereinafter.
[0070] The ratio of the initial laser transmittance at 780 nm to the initial laser transmittance at 1064 nm is specifically determined according to UV-visible spectrophotometry measurements as described in the Examples below.
[0071] Useful black colorants may be particularly selected from perylene-derived pigments comprising isomers having formula Ia, isomers having formula Ib, or combinations thereof
[0072]
[0073] in
[0074] R 1 , R 2are each independently 1,2-phenylene, 1,8-, 1,2- or 2,3-naphthylene or 2,3- or 3,4-pyridylene, each optionally substituted by C1-C 12 - alkyl, C1-C6-alkoxy, hydroxy, nitro and / or halogen mono- or polysubstituted,
[0075] X is halogen, in particular chlorine or bromine, and
[0076] n is 0 to 4.
[0077] In Formulas Ia and Ib, R 1 and R 2 The phenylene, naphthylene and pyridylene groups can be replaced by C1-C 12 - alkyl, especially C1-C4-alkyl, C1-C6-alkoxy, especially C1-C4-alkoxy, hydroxy, nitro and / or halogen, especially chlorine or bromine, mono- or polysubstituted.
[0078] Alternatively, in Formulas Ia and Ib, as R 1 and R 2 The phenylene, naphthylene and pyridylene groups may be unsubstituted. 1 , R 2 are each independently an unsubstituted 1,2-phenylene or 1,8-naphthylene. More preferably, R 1 and R 2 are the same and are selected from unsubstituted 1,2-phenylene or 1,8-naphthylene.
[0079] Useful perylene-derived pigments specifically include isomers having Formula Ia, isomers having Formula Ib, or combinations thereof, wherein R 1 , R 2 are the same and are selected from unsubstituted 1,2-phenylene or 1,8-naphthylene, and n is 0.
[0080] Perylene-derived pigments can be prepared by known methods, for example as described in patent application WO2005078023A3, which is incorporated herein by reference.
[0081] The black colorant may be present in the molding composition according to the invention in an amount of 0.01 to 0.5% by weight, preferably 0.03 to 0.3% by weight, more preferably 0.04 to 0.2% by weight, for example 0.05%, 0.1% or 0.2% by weight, based on the total weight of the molding composition.
[0082] Component (C)
[0083] Optionally, the molding composition according to the present invention may further comprise a reinforcing agent as component (C), which may be of different types without particular limitation, such as fibers, whiskers, flakes and particles.
[0084] Useful reinforcing agents may in particular be chosen from fibrous reinforcements and particulate fillers.
[0085] Examples of fiber reinforcements may include, but are not limited to, glass fibers, carbon fibers, boron fibers, asbestos fibers, polyvinyl alcohol fibers, polyester fibers, acrylic fibers, wholly aromatic polyamide fibers, polybenzoxazole fibers, polytetrafluoroethylene fibers, kenaf fibers, bamboo fibers, hemp fibers, bagasse fibers, high-strength polyethylene fibers, alumina fibers, silicon carbide fibers, potassium titanate fibers, brass fibers, stainless steel fibers, steel fibers, ceramic fibers, wollastonite fibers, and basalt fibers, with glass fibers and carbon fibers being particularly preferred.
[0086] There are no particular restrictions on the fiber length and fiber diameter of the fiber reinforcement. For example, short-cut fibers or continuous fibers with a length in the range of 1 to 10 mm, preferably 2 to 6 mm, can be used as the starting material of the reinforcement. The fibers will decompose during processing (e.g. kneading the molding composition) to a length of several hundred microns as present in the obtained molding. The fiber diameter is generally in the range of 3 to 20 μm, preferably 7 to 13 μm.
[0087] Examples of the cross-sectional shape of the fiber reinforcement include, for example, circular, rectangular, elliptical, and other non-circular shapes, with the circular shape being particularly preferred. The fiber reinforcement may have a cross-section with an aspect ratio ranging from 1:1 to 5:1.
[0088] Glass fiber is particularly useful as a fiber reinforcement for the present invention. The glass fiber may have been surface treated with a silane coupling agent (such as a coupling agent based on vinyl silane, a coupling agent based on acrylic silane, a coupling agent based on epoxy silane, and a coupling agent based on amino silane, preferably a coupling agent based on amino silane). The silane coupling agent may be dispersed in a sizing agent. Examples of sizing agents are acrylic compounds, acrylic acid / maleic acid derivative modified compounds, epoxy compounds, urethane compounds, urethane / maleic acid derivative modified compounds, and urethane / amine modified compounds.
[0089] The particulate filler can be organic or inorganic filler and has a variety of particle sizes, ranging from particles in the form of dust to coarse particles. Examples of materials that can be used as inorganic particulate fillers include, but are not limited to, kaolin, chalk, wollastonite, talc, calcium carbonate, silicates, titanium dioxide, zinc oxide, graphite, mica, vermiculite, montmorillonite and glass particles (e.g., glass beads).
[0090] In some embodiments, the reinforcing agent as component (C) is selected from glass fibers. The glass fibers can be, for example, E-glass fibers, A-glass fibers, D-glass fibers, AR-glass fibers, C-glass fibers and S-glass fibers, or any other high modulus or high strength glass fibers such as M-glass fibers and HMG glass fibers.
[0091] The reinforcing agent, if included, may be present in the molding composition according to the invention in an amount of 0.5 to 50% by weight, preferably 10 to 40% by weight, more preferably 20 to 40% by weight, for example 20%, 25%, 30%, 35% or 40% by weight, based on the total weight of the molding composition.
[0092] Component (D)
[0093] Alternatively, the molding composition according to the present invention may further comprise, as component (D), an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof.
[0094] Useful amorphous polymeric materials may have a refractive index of at least 1.55, preferably in the range of 1.55 to 1.6, as measured according to ASTM D542 at 25°C and a wavelength of 589 nm.
[0095] Useful amorphous polystyrenes may be polymers comprising at least 50% by mole, preferably at least 60% by mole, most preferably at least 70% by mole of units derived from substituted or unsubstituted styrene monomers.
[0096] Examples of substituted or unsubstituted styrene monomers include, but are not limited to, styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, p-α-dimethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-isopropylstyrene, 3-isopropylstyrene, 4-isopropylstyrene, o-divinylbenzene, m-divinylbenzene, p-divinylbenzene, ethoxystyrene, chlorostyrene, bromostyrene, dibromostyrene, dichlorostyrene, tribromostyrene, trichlorostyrene, 2-vinylnaphthalene, 2-isopropenylnaphthalene, or any combination thereof, preferably styrene, α-methylstyrene, 4-methylstyrene, chlorostyrene, p-divinylbenzene, bromostyrene, dibromostyrene, trichlorostyrene, 2-vinylnaphthalene, 2-isopropenylnaphthalene, or any combination thereof, more preferably styrene, α-methylstyrene, 4-methylstyrene,
[0097] Generally, useful amorphous polystyrenes may have a weight average molecular weight (Mw) ranging from 50,000 to 300,000, preferably from 100,000 to 200,000, as determined by GPC.
[0098] It should be understood that the term "polystyrene" is not intended to include "styrene-acrylonitrile copolymers" as used herein.
[0099] Useful amorphous styrene-acrylonitrile copolymers are copolymers derived from substituted or unsubstituted styrene monomers and substituted or unsubstituted vinyl cyanide monomers. The substituted or unsubstituted styrene monomers may be selected from those described above, preferably styrene, α-methylstyrene, 4-methylstyrene, 4-chloro-styrene or any combination thereof. The vinyl cyanide monomer may be acrylonitrile, methacrylonitrile or a combination thereof.
[0100] The styrene-acrylonitrile copolymer may include 50 to 99% by weight of a substituted or unsubstituted styrene monomer and 1 to 50% by weight of a substituted or unsubstituted vinyl cyanide monomer.
[0101] The styrene-acrylonitrile copolymer may further comprise a comonomer selected from C1-C8 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate or other unsaturated carboxylic acid derivatives such as anhydrides or imides thereof, in particular maleic anhydride or n-phenylmaleimide.
[0102] Examples of styrene-acrylonitrile copolymers include, but are not limited to, copolymers of styrene / acrylonitrile (SAN copolymer), α-methylstyrene / acrylonitrile (AMSAN copolymer), styrene / acrylonitrile / maleic anhydride, styrene / acrylonitrile / phenylmaleimide, α-methylstyrene / acrylonitrile / methyl methacrylate, α-methyl-styrene / acrylonitrile / t-butyl methacrylate, styrene / acrylonitrile / t-butyl methacrylate, or any combination thereof.
[0103] The styrene-acrylonitrile copolymer may have a weight average molecular weight (Mw) of 150,000 to 350,000, preferably 150,000 to 300,000, more preferably 150,000 to 250,000, and most preferably 150,000 to 200,000 as measured by GPC.
[0104] Useful amorphous polyester copolymers may be those having at least two different repeating units (RP1 and RP2), the combined amount of which is at least 55% by mole, preferably at least 80% by mole, more preferably at least 90% by mole, based on the total repeating units of the polyester copolymer. The repeating unit RP1 is derived from a diol monomer and a dicarboxylic acid monomer, wherein the dicarboxylic acid monomer comprises terephthalic acid and optionally another dicarboxylic acid. The repeating unit RP2 is derived from a diol monomer and a dicarboxylic acid monomer. The molar ratio of the diol moiety in RP1 to the diol moiety in RP2 is preferably 2:8 to 8:2.
[0105] The diol monomers used to obtain the units RP1 and RP2 can be independently selected from aliphatic diols having 2 to 12 carbon atoms, alicyclic diols having 4 to 12 carbon atoms, or any combination thereof. Examples of aliphatic diols having 2 to 12 carbon atoms include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,6-hexanediol, neopentyl glycol, 1,3-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, ditetramethylene glycol and decanediol, more preferably ethylene glycol, diethylene glycol and neopentyl glycol. Examples of the alicyclic diol having 4 to 12 carbon atoms include 1,2-cyclobutanediol, 1,3-cyclobutanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and bis-1,4-(hydroxymethyl)cyclohexane, with 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol being more preferred.
[0106] Another dicarboxylic acid for obtaining unit RP1 and the dicarboxylic acid for obtaining unit RP2 can be independently selected from aliphatic dicarboxylic acids with 2 to 20 carbon atoms, alicyclic dicarboxylic acids with 7 to 12 carbon atoms, aromatic dicarboxylic acids or any combination thereof. The example of aliphatic dicarboxylic acids with 2 to 20 carbon atoms includes succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, undecane dioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanoic acid and hexadecanedioic acid, more preferably succinic acid, glutaric acid, adipic acid and pimelic acid. The example of alicyclic dicarboxylic acids with 7 to 12 carbon atoms includes 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid and 1,3-cyclopentanedicarboxylic acid. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid and phthalic acid.It will be appreciated that the other dicarboxylic acid in RP1 is not terephthalic acid.
[0107] The diol monomer used to obtain unit RP1 is preferably selected from aliphatic diols having 2 to 12 carbon atoms, more preferably ethylene glycol, diethylene glycol, neopentyl glycol or any combination thereof. The diol monomer used to obtain unit RP2 is preferably selected from alicyclic diols having 6 to 12 carbon atoms, preferably 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol or a combination thereof. Preferably, the dicarboxylic acid monomer used to obtain unit RP2 is terephthalic acid, and another dicarboxylic acid monomer used to obtain unit RP1 is absent.
[0108] In some embodiments, unit RP1 is derived from ethylene glycol and terephthalic acid, while unit RP2 is derived from 1,4-cyclohexanedimethanol and terephthalic acid. The molar ratio of ethylene glycol to 1,4-cyclohexanedimethanol is preferably in the range of 8:2 to 7:3. Such amorphous polyester copolymers are also known as PETG (cyclohexanedimethylene glycol modified polyethylene terephthalate).
[0109] In some other embodiments, RP1 is derived from ethylene glycol and terephthalic acid, and RP2 is derived from 1,4-cyclohexanedimethanol and terephthalic acid. The molar ratio of ethylene glycol to 1,4-cyclohexanedimethanol is preferably 2:8 to 3:7. Such amorphous polyester copolymers are also known as PCTG (ethylene glycol-modified poly (1,4-cyclohexanedimethylene terephthalate)).
[0110] PETG and PCTG are commercially available, for example, from Eastman Chemical Co. and SK Chemicals Co. Ltd, such as SK Chemicals Co. Ltd. S2008, Easter 6763 and Easter 5445 from Eastman Chemical Company.
[0111] Useful amorphous polyamides can be, for example, block copolymers, random copolymers, graft copolymers or alternating copolymers. Examples of amorphous polyamides can include, but are not limited to, PA6I, PA6T, PA6 / PA66, PA66 / 6, PA6 / 510, PA56 / 66, PA56 / 6, PA5T / 66, PA5T / 6, PA6 / 610, PA6 / 612, PA6 / 636, PA6 / 1010, PA66 / 410, PA66 / 510, PA66 / 610, PA66 / 612, PA 66 / 1010, PA6T / 66, PA6T / 6, PA6I / 6T, PA56 / 5T, PA5T / 56, PA6 / 6T, PA66 / 6T and PA6T / 6I, among which PA6I, PA6 / PA66, PA66 / 6, PA6T / 66, PA66 / 6T, PA6T / 6I and PA6I / 6T are preferred, among which PA6I, PA6I / 6T or a combination thereof is more preferred.
[0112] In some specific embodiments, the molding composition according to the present invention comprises an amorphous polymer material selected from a combination of polystyrene and PETG. Polystyrene and PETG may be present in a weight ratio ranging from 10:1 to 1:10, preferably 5:1 to 1:5, more preferably 3:1 to 1:3, for example 2:1, 1:1 or 1:2. In those embodiments, the molding composition according to the present invention preferably comprises a crystalline polymer material selected from polyester or a blend containing polyester as component (A).
[0113] In some other specific embodiments, the molding composition according to the present invention comprises an amorphous polymer material selected from amorphous polyamides, in particular PA6I, PA6I / 6T or a combination thereof. In those embodiments, the molding composition according to the present invention preferably comprises a crystalline polymer material selected from polyamides or blends containing polyamides as component (A).
[0114] Amorphous polymer material, if included, is present in the molding composition according to the invention in a total amount of 1 to 50% by weight, preferably 10 to 40% by weight, more preferably 15 to 35% by weight, for example 15%, 20%, 25%, 30% or 35% by weight, based on the total weight of the molding composition.
[0115] Component (E)
[0116] Optionally, the molding composition according to the present invention may further comprise one or more additives as component (E), such as nucleating agents, mold release agents, impact modifiers, heat stabilizers, light stabilizers, compatibilizers, lubricants, antioxidants, adhesive adjuvants, plasticizers, colorants other than component (B), surfactants, flame retardants, flame retardant synergists, coupling agents, antimicrobial agents, antistatic agents, etc.
[0117] The molding composition according to the invention may, for example, contain a nucleating agent. Suitable nucleating agents may be selected from talc, boron nitride, mica, kaolin, alkali metal or alkaline earth metal carbonates, bicarbonates or sulfates, alkali metal titanates, silicon nitride or molybdenum disulfide. The nucleating agent is preferably selected from alkali metal carbonates, alkali metal bicarbonates or any combination thereof.
[0118] In some embodiments, the molding composition according to the present invention comprises an alkali metal carbonate or bicarbonate as one of the additives of component (E), preferably sodium carbonate (Na2CO3), potassium carbonate (K2CO3), sodium bicarbonate (NaHCO3) and potassium bicarbonate (KHCO3), among which sodium carbonate is most preferred.
[0119] The nucleating agent, if included, may be present in an amount of 0.01% to 10% by weight, preferably 0.05% to 6% by weight, more preferably 0.1% to 2% by weight or 0.1% to 0.5% by weight, for example 0.1%, 0.15%, 0.2%, 0.3%, 0.4% or 0.5% by weight, based on the total weight of the molding composition.
[0120] The molding composition according to the invention may, for example, contain a lubricant. Suitable lubricants may be selected from esters or amides of saturated aliphatic carboxylic acids having 10 to 40 carbon atoms, saturated aliphatic alcohols having 2 to 40 carbon atoms or amines, or any combination thereof. The lubricant is preferably a pentaerythritol ester of a fatty acid having 10 to 20 carbon atoms, more preferably pentaerythritol tetrastearate. The lubricant, if contained, may be present in an amount of 0.01% to 3%, for example 0.1% to 2%, or 0.2% to 1%, by weight based on the total weight of the molding composition.
[0121] The molding composition according to the present invention may, for example, contain an antioxidant. Suitable antioxidants may be selected from antioxidants based on aromatic amines, antioxidants based on hindered phenols, antioxidants based on phosphites, or any combination thereof, in particular antioxidants based on hindered phenols. Examples of hindered phenol-based antioxidants include α-[3-[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropyl]-ω-[3-[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropoxy]poly(oxy-1,2-ethanediyl), 2,4-bis[(octylthio)methyl]-o-cresol, octyl-3,5-di-tert-butyl-4-hydroxy-hydrocinnamate, 3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropanoic acid C 7-9 -branched alkyl esters, 2,4-bis[(dodecylthio)methyl]-o-cresol, 4,4'-butylenebis-(3-methyl-6-tert-butylphenol), 3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate octadecyl ester, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydrophenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, tris-(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and 2,2-thiodiethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. The antioxidant, if included, may be present in an amount of 0% to 2% by weight, or 0.01% to 1% by weight, or 0.2% to 0.8% by weight, based on the total weight of the molding composition.
[0122] The molding composition according to the invention may, for example, contain an adhesive auxiliary. Suitable adhesive auxiliary agents may be selected from epoxides, for example epoxidized fatty acid alkyl esters such as epoxidized linseed oil, epoxidized soybean oil and epoxidized rapeseed oil, epoxy resins such as bisphenol-A resins or any combination thereof. The adhesive auxiliary agent (if included) may be present in an amount of 0% to 2% by weight, for example 0.01% to 1% by weight or 0.2% to 0.8% by weight, based on the total weight of the molding composition.
[0123] Preparations
[0124] It will be understood that any options for the general or preferred substances and / or amounts of components (A), (B), (C), (D) and (E) as described herein can be combined in any manner without limitation. For example, a general range for the amount of one component combined with any preferred range for the amount of other components, or a preferred range for the amount of one component combined with a general range for the amount of other components, etc. are included in the present invention.
[0125] The following examples will be described as examples of formulations of the molding compositions according to the invention.
[0126] In some embodiments, the molding composition according to the present invention comprises
[0127] (A) 30% to 80% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0128] (B) 0.03% to 0.3% by weight of a black colorant,
[0129] (C) 0% to 50% by weight of a reinforcing agent, and
[0130] (D) 0% to 50% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0131] (E) 0% to 10% by weight of one or more additives,
[0132] each based on the total weight of the molding composition,
[0133] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0134] Preferably, the molding composition according to the invention comprises
[0135] (A) 35% to 75% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0136] (B) 0.04% to 0.2% by weight of a black colorant,
[0137] (C) 0% to 50% by weight of a reinforcing agent, and
[0138] (D) 0% to 50% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0139] (E) 0% to 10% by weight of one or more additives,
[0140] each based on the total weight of the molding composition,
[0141] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0142] In some other embodiments, the molding composition according to the present invention comprises
[0143] (A) 30% to 80% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0144] (B) 0.03% to 0.3% by weight of a black colorant,
[0145] (C) 0% to 50% by weight of a reinforcing agent, and
[0146] (D) 10% to 40% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0147] (E) 0% to 10% by weight of one or more additives,
[0148] each based on the total weight of the molding composition,
[0149] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0150] Preferably, the molding composition according to the invention comprises
[0151] (A) 30% to 80% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0152] (B) 0.03% to 0.3% by weight of a black colorant,
[0153] (C) 10 to 40% by weight of a reinforcing agent, and
[0154] (D) 10% to 40% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0155] (E) 0% to 10% by weight of one or more additives,
[0156] each based on the total weight of the molding composition,
[0157] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0158] More preferably, the molding composition according to the invention comprises
[0159] (A) 35% to 75% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0160] (B) 0.04% to 0.2% by weight of a black colorant,
[0161] (C) 10 to 40% by weight of a reinforcing agent, and
[0162] (D) 10% to 40% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0163] (E) 0% to 10% by weight of one or more additives,
[0164] each based on the total weight of the molding composition,
[0165] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0166] In some specific embodiments, the molding composition according to the present invention comprises
[0167] (A) 35 to 75% by weight of a crystalline polymer material selected from a polyamide or a blend containing a polyamide,
[0168] (B) 0.04% to 0.2% by weight of a black colorant selected from perylene-derived pigments including isomers of Formula Ia, isomers of Formula Ib, or combinations thereof as described herein,
[0169] (C) 10 to 40% by weight of a reinforcing agent, and
[0170] (D) 10 to 40% by weight of an amorphous polymer material selected from polyamides, and
[0171] (E) 0% to 10% by weight of one or more additives,
[0172] each based on the total weight of the molding composition,
[0173] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0174] In some other specific embodiments, the molding composition according to the present invention comprises
[0175] (A) 35% to 75% by weight of a crystalline polymer material selected from polyesters or blends containing polyesters,
[0176] (B) 0.04% to 0.2% by weight of a black colorant selected from perylene-derived pigments including isomers of Formula Ia, isomers of Formula Ib, or combinations thereof as described herein,
[0177] (C) 10 to 40% by weight of a reinforcing agent, and
[0178] (D) 10% to 40% by weight of amorphous polystyrene and a polyester copolymer selected from PETG, PCTG or a combination thereof, and
[0179] (E) >0 to 10% by weight of one or more additives, including 0.01 to 10% by weight, preferably 0.05 to 6% by weight, more preferably 0.1 to 2% by weight or 0.1 to 0.5% by weight of a nucleating agent,
[0180] each based on the total weight of the molding composition,
[0181] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0182] In those embodiments described above as examples of formulations of the molding composition according to the invention, the ratio of the laser transmittance at 780 nm to the laser transmittance at 1064 nm is preferably in the range of less than 10% or even less than 5%.
[0183] The molding composition according to the present invention can be processed by any conventional method without particular restrictions. For example, the molding composition can be processed by mixing and kneading these components in any conventional kneading device (such as a single screw or twin screw extruder, a Brabender mixer or a Banbury mixer). It is also possible to add the other components as a premix with the polyamide resin component or in turn with the polyamide resin component to the polymer material as component (A), wherein a reinforcing agent such as glass fiber (if used) is preferably side-fed into the kneading device. Mixing and kneading can preferably be carried out at a temperature in the range of 220° C. to 290° C. The obtained mixture can be cooled and pulverized.
[0184] Any conventional molding method may be applied to the molding composition according to the present invention to provide a plastic part or article, such as injection molding, hollow molding, extrusion molding and compression molding.
[0185] <Use of molding composition>
[0186] The molding compositions as described herein are particularly useful for making laser transparent plastic parts or articles to be processed by laser welding or laser marking.
[0187] For laser welding applications, the molding composition can be processed into a molded part and then subjected to any conventional laser welding process without particular limitation, as a laser transparent part to be bonded to a laser absorbing part.
[0188] For laser absorbing parts, any laser absorbing plastic material can be used without particular limitation. For example, composite materials or thermosetting materials can be used, but thermoplastic compositions are preferred. Suitable thermoplastic compositions are those that have sufficient laser absorption in the wavelength range used. Examples of suitable thermoplastic compositions include thermoplastic polymers and laser absorbing fillers, preferably those that exhibit maximum absorption in the wavelength range of 780nm to 1100nm, especially 900nm to 1100nm, such as inorganic pigments such as carbon black, and / or organic pigments or other light absorbing fillers such as glass fibers, carbon fibers, silica, alumina, talc, wherein carbon black is preferred.
[0189] Conventional thermoplastic polymers may be used without limitation, such as polyamides, olefin polymers, vinyl-based polymers, styrene-based polymers, acrylic polymers, polyphenylene ethers, polyesters, polycarbonates, polyacetals, or any combination thereof.
[0190] <Products>
[0191] Thus, the present invention provides an article produced using a molding composition as described herein.
[0192] The articles according to the present invention can be used in various applications, for example in storage containers, electrical / electronic equipment, office automation (OA) equipment, household appliances, automotive devices or parts. Particularly preferred applications include automotive hollow parts (such as tanks, intake manifolds, camera housings and radar housings), automotive electronic parts (such as control units and ignition coils), sensor devices, connectors. The articles according to the present invention are particularly suitable as housings for automotive radars or automotive cameras.
[0193] Example
[0194] Various embodiments are listed below. It will be understood that the embodiments listed below can be combined with all aspects of the scope of the present invention and other embodiments.
[0195] 1. A molding composition comprising
[0196] (A) 20% to 98% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof,
[0197] (B) 0.01 to 0.5% by weight of a black colorant,
[0198] (C) 0% to 50% by weight of a reinforcing agent, and
[0199] (D) 0% to 50% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and
[0200] (E) 0% to 10% by weight of one or more additives,
[0201] each based on the total weight of the molding composition,
[0202] The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen.
[0203] 2. The molding composition of embodiment 1, wherein the ratio of the initial laser transmittance at 780 nm to the initial laser transmittance at 1064 nm is in the range of less than 10%.
[0204] 3. The molding composition of embodiment 2, wherein the ratio of the initial laser transmittance at 780 nm to the initial laser transmittance at 1064 nm is in the range of less than 5%.
[0205] 4. The molding composition according to any one of the preceding embodiments, comprising as component (B) a black colorant selected from perylene-derived pigments comprising isomers having Formula Ia, isomers having Formula Ib, or a combination thereof
[0206]
[0207] in
[0208] R 1 , R 2 are each independently 1,2-phenylene, 1,8-, 1,2- or 2,3-naphthylene or 2,3- or 3,4-pyridylene, each optionally substituted by C1-C 12 - alkyl, C1-C6-alkoxy, hydroxy, nitro and / or halogen mono- or polysubstituted,
[0209] X is halogen, in particular chlorine or bromine, and
[0210] n is 0 to 4.
[0211] 5. The molding composition of embodiment 4, wherein the phenylene, naphthylene and pyridylene groups are unsubstituted.
[0212] 6. The molding composition according to embodiment 5, wherein R 1 and R 2 Each is independently an unsubstituted 1,2-phenylene or 1,8-naphthylene.
[0213] 7. The molding composition according to embodiment 4 or 5, wherein R 1 and R 2 same.
[0214] 8. The molding composition of any one of embodiments 4 to 7, wherein n is 0.
[0215] 9. The molding composition of any of the preceding embodiments, comprising as component (A) a crystalline polymer material selected from polyamides or blends containing polyamides.
[0216] 10. The molding composition according to embodiment 9, comprising as component (D) an amorphous polymer material selected from polyamides.
[0217] 11. The molding composition according to any one of the preceding embodiments, comprising as component (A) a crystalline polymer material selected from polyamide or a blend containing polyamide and as component (D) an amorphous polymer material selected from PA 6I, PA6I / 6T or a combination thereof.
[0218] 12. The molding composition according to any one of the preceding embodiments 1 to 8, comprising as component (A) a crystalline polymer material selected from polyesters or blends containing polyesters.
[0219] 13. The molding composition according to embodiment 12, comprising as component (A) a polyalkylene terephthalate or a blend comprising a polyalkylene terephthalate.
[0220] 14. The molding composition of any of the preceding embodiments 10 or 11, comprising as component (D) a combination of a polyester copolymer selected from PETG, PCTG, or a combination thereof, and polystyrene.
[0221] 15. The molding composition of embodiment 14, comprising as component (D) a combination of polystyrene and PETG.
[0222] 16. The molding composition of any of the preceding embodiments 12 to 15, comprising a polyalkylene terephthalate or a blend containing a polyalkylene terephthalate as component (A) and a combination of polystyrene and PETG as component (D).
[0223] 17. The molding composition according to any of the preceding embodiments, wherein the component (E) comprises a nucleating agent, preferably selected from alkali metal carbonates, alkali metal bicarbonates, or any combination thereof, more preferably sodium carbonate, sodium bicarbonate, or a combination thereof.
[0224] 18. The molding composition of any preceding embodiment, wherein component (B) comprises glass fibers.
[0225] 19. The molding composition of any preceding embodiment, wherein component (A) is present in an amount of 30 to 80% by weight.
[0226] 20. The molding composition of embodiment 19, wherein component (A) is present in an amount of 35 to 75% by weight.
[0227] 21. The molding composition of any preceding embodiment, wherein component (B) is present in an amount of 0.03% to 0.3% by weight.
[0228] 22. The molding composition of embodiment 21, wherein component (B) is present in an amount of 0.04 to 0.2% by weight.
[0229] 23. The molding composition of any preceding embodiment, wherein component (C) is present in an amount of 0.5% to 50% by weight.
[0230] 24. The molding composition of embodiment 23, wherein component (C) is present in an amount of 10 to 40% by weight.
[0231] 25. The molding composition of embodiment 24, wherein component (C) is present in an amount of 20 to 40% by weight.
[0232] 26. The molding composition of any preceding embodiment, wherein component (D) is present in an amount of 1 to 50% by weight.
[0233] 27. The molding composition of embodiment 26, wherein component (D) is present in an amount of 10 to 40% by weight.
[0234] 28. The molding composition of embodiment 27, wherein component (D) is present in an amount of 15 to 35% by weight.
[0235] 29. The molding composition of any preceding embodiment, wherein the component (E) is present and comprises a nucleating agent in an amount of 0.01 to 10% by weight, based on the total weight of the molding composition.
[0236] 30. The molding composition of embodiment 29, wherein the component (E) comprises a nucleating agent in an amount of 0.05 to 6% by weight, based on the total weight of the molding composition.
[0237] 31. The molding composition of embodiment 30, wherein component (E) comprises a nucleating agent in an amount of 0.1 to 2% by weight, based on the total weight of the molding composition.
[0238] 32. The molding composition of embodiment 31, wherein component (E) comprises a nucleating agent in an amount of 0.1 to 0.5% by weight, based on the total weight of the molding composition.
[0239] 33. Use of the molding composition according to any one of the preceding embodiments for producing laser-transparent plastic parts or articles.
[0240] 34. Article produced using the molding composition according to any one of the preceding embodiments 1 to 31, such as a housing for an automotive radar or automotive camera.
[0241] Examples
[0242] Various aspects of the present invention will be more fully described by the following examples, which are presented for the purpose of illustrating certain aspects of the present invention and should not be construed as limiting thereof.
[0243] Unless otherwise stated, preparations and measurements as described herein were performed in an air atmosphere at ambient temperature and humidity.
[0244] Material
[0245] PA66: U 4800NC01, a crystalline polyamide 66 available from Invista;
[0246] PA6I: TM01, amorphous polyamide 6I, available from Shandong Dongchen New Technology Co. Ltd;
[0247] PA6I / 6T: TI1207, amorphous polyamide 6I / 6T, available from Shandong Guangyin New Materials Co. Ltd;
[0248] PBT: B 4500, a crystalline polybutylene terephthalate available from BASF SE, having a terminal carboxyl content of 34 meq / kg and an intrinsic viscosity of 130 ml / g, as measured in a 0.5 wt% strength phenol / o-dichlorobenzene solution (1:1 mixture) at 25° C.;
[0249] PS: PG-383M, amorphous polystyrene, available from CHIMEI Corporation;
[0250] PETG: S2008, available from SK Chemical Co., Ltd.;
[0251] Glass fiber: (1) ECS 301HP-3-H, E-glass fiber, available from Chongqing Polycomp International Corp.; (2) PBT-NEG-T187H, E-glass fiber, available from Nippon Electric Glass Co., Ltd.;
[0252] Heat Stabilizer: 101, masterbatch of KI and CuI, available from BASF;
[0253] Lubricant: CRODAMIDE EBS TM , ethylene-bis-stearamide, available from Croda;
[0254] Nigrosine: COLORANT BLACK 500, available from Orient Chemical Co. Ltd;
[0255] Green 5B Gran: a solvent-soluble anthraquinone-type green dye available from LANXESS;
[0256] Red E2G Gran: solvent-soluble pyrene-type red dye, available from LANXESS;
[0257] Perylene-derived pigment 1: an isomeric mixture of black pigments having formula 1a and 1b, wherein R 1 =R 2 =1,8-naphthylene and n is 0, as prepared according to the method described in Example 2 of WO 2005078023A3;
[0258] Perylene-derived pigment 2: an isomeric mixture of black pigments having formula 1a and 1b, wherein R 1 =R 2 =1,2-phenylene and n is 0, as prepared according to the method described in Example 1 of WO 2005078023A3.
[0259] Preparation of test specimens
[0260] Injection molded test sheets with dimensions of 60 mm x 60 mm x 2 mm (length x width x thickness) and edge gates were prepared by injection molding according to the formulations specified in the following table, with the parameters set to the following values:
[0261]
[0262] The injection molded sheet was used as a sample sheet for the following measurement.
[0263] Laser transmittance measurement
[0264] 1) Thermoelectric power measurement
[0265] The laser transmittance shown in Table 1 below was determined at a wavelength of 1064 nm by thermoelectric power measurement. The measurement geometry was set up as follows. A beam splitter (SQ2 non-polarizing beam splitter from Laseroptik GmbH) was used to separate a reference beam with a power of 1 W at an angle of 90° from a laser beam with a total power of 2 W (diode-pumped Nd-YAG laser with a wavelength of 1064 nm, FOBA Vario S50; laser source type DP50). The reference beam acts on a reference sensor. The part of the original beam that passes through the beam splitter provides a measurement beam with a power of the same 1 W. This beam is focused to a focal spot diameter of 0.18 μm by a mode aperture (5.0) behind the beam splitter. The laser transparency (LT) measurement sensor is located 80 mm below the focus. The test sheet is located 2 mm above the LT measurement sensor. The total measurement time is 30 seconds, and the measurement results are determined within the last 5 seconds. The signals from the reference sensor and the measurement sensor are captured simultaneously. The start of the measurement is simultaneous with the insertion of the sample. The measurement is made in the middle of the sample sheet (intersection of the two diagonal lines).
[0266] The laser transmittance (LT) is obtained according to the following formula:
[0267]
[0268] in
[0269] Signal 1 is a signal captured by a measuring sensor; and
[0270] Signal 2 is the signal captured by the reference sensor.
[0271] The results are reported as the average LT value calculated from five measurements of the sheet. For each material, the average is calculated for 10 sheets.
[0272] 2) UV-Visible Spectrophotometry
[0273] UV-visible spectrophotometer (Mettler Evolution TM 220) were measured for laser transmittance as shown in the table below. The results are reported as the average LT value calculated from five measurements of the sheet. For each material, the average was calculated for 10 sheets.
[0274] Laser marking and contrast measurement
[0275] The sample sheets were marked by a LS-U model LAISAI laser marker from Laser Technology Co., Ltd using a laser beam at 355 nm. The printability of the sample sheets was characterized by the contrast ratio as obtained according to the following formula,
[0276]
[0277] in
[0278] LS 标记 represents the brightness intensity of the brightest marker generated, and
[0279] LS 背景 Represents the brightness intensity of the unlabeled background.
[0280] The brightness intensity was measured by a Konica Minolta LS-160 brightness meter.
[0281] UV aging resistance measurement
[0282] The sample sheets were subjected to UV exposure according to ISO 4892-2:2013 for the specified durations as shown in the table below and passed the ΔE ab The values and grayscale characterize the resistance to UV aging. The test pieces are measured initially, immediately after the specified duration, within 1 hour, and at the end of exposure.
[0283] ΔEab values are measured according to ASTM D2244-16 by using an X-rite Ci6X spherical spectrophotometer under D65 standard light with a 10° observer and an 8 mm aperture. The results are reported as ΔEab SCE (excluding specular reflection) and ΔEab SCI (including specular reflection).
[0284] Grayscale is measured under D65 standard light according to GB / T 250-2008. The results are reported as rating numbers, where 5 is the best and 1 is the worst.
[0285] The formulations and test results of the polyamide-containing molding compositions are summarized in Table 1 below.
[0286] Table 1
[0287]
[0288]
[0289] 1) LT value measured by thermoelectric power
[0290] 2) LT values measured by UV-visible spectrophotometry
[0291] Compared to sample C2 containing nigrosine (a commonly used black colorant), samples E1 and E2 according to the present invention achieve similar blackness but provide much higher laser transmittance. Surprisingly, samples E1 and E2 exhibit much better UV resistance than samples C2 and C3, although the latter exhibit higher laser transmittance.
[0292] The laser transmittance of the samples according to the present invention can be further significantly improved by incorporating amorphous polymer materials.
[0293] It has also been unexpectedly found that samples E1 and E2 exhibit better laser printability in a laser marking process than samples C2 and C3, as evidenced by the marking contrast results in Table 1. The better printability of samples E1 and E2 can also be directly derived from the Figure 1 The excellent laser printability of samples E1 and E2 can be attributed to their opacity to laser light in the UV range, which is unexpected because conventional laser transparent plastic materials fail to exhibit satisfactory laser printability while exhibiting desirable laser transmittance.
[0294] The formulations and test results of the molding compositions comprising polyesters are summarized in Tables 2 and 3 below.
[0295] Table 2
[0296]
[0297]
[0298] 2) LT values measured by UV-visible spectrophotometry
[0299] It can be seen that samples E5 and E6 according to the present invention exhibit comparable laser transmittance to sample C4 containing a conventional combination of red and green dyes, even at much lower dosages (E5 vs. C4). Similar results can be seen from a comparison between samples E7 to E9 according to the present invention and sample C5.
[0300] It has also been unexpectedly discovered that laser transmittance can be significantly improved by incorporating amorphous polymer materials.
[0301] Table 3
[0302]
[0303]
[0304] The inventors have found that conventional UV absorbers or stabilizers for plastic materials (e.g., PBT), such as Tinuvin-234 (benzotriazole UV absorber), Hostavin N30 P (oligomeric hindered amine light stabilizer), and Tinuvin 770DF (solid basic hindered amine light stabilizer), do not provide effective protection for colorant-containing laser transparent plastic materials from color shift due to UV aging, as evidenced by the high ΔEab values of samples C6 to C9. Unexpectedly, the UV aging resistance of laser transparent plastic materials was successfully improved by using perylene-derived pigments, as evidenced by lower ΔEab values and higher grayscale (C4 vs. E10).
[0305] It will be apparent to those skilled in the art that various modifications and variations may be made in the present invention without departing from the scope or spirit of the present invention. It is intended that the embodiments and examples be considered illustrative only. Therefore, the present invention is intended to cover such modifications and variations within the scope of the appended claims and their equivalents.
Claims
1. A molding composition comprising (A) 20% to 98% by weight of a crystalline polymer material selected from the group consisting of polyamides, polyesters, blends containing polyamides, blends containing polyesters, or any combination thereof, (B) 0.01 to 0.5% by weight of a black colorant, (C) 0% to 50% by weight of a reinforcing agent, and (D) 0% to 50% by weight of an amorphous polymer material selected from polystyrene, styrene-acrylonitrile copolymer, polyester copolymer, polyamide, or any combination thereof, and (E) 0% to 10% by weight of one or more additives, each based on the total weight of the molding composition, The molding composition has an initial laser transmittance at 1064 nm of at least 20%, and a ratio of initial laser transmittance at 780 nm to initial laser transmittance at 1064 nm in the range of less than 20%, as measured in the form of a 2-mm thick test specimen. 2 . The molding composition according to claim 1 , wherein the ratio of the initial laser transmittance at 780 nm to the initial laser transmittance at 1064 nm is in the range of less than 10% or even less than 5%.
3. The molding composition according to any one of the preceding claims, comprising as component (B) a black colorant selected from perylene-derived pigments comprising isomers having formula Ia, isomers having formula Ib, or a combination thereof in R 1 , R 2 are each independently 1,2-phenylene, 1,8-, 1,2- or 2,3-naphthylene or 2,3- or 3,4-pyridylene, each optionally substituted by C1-C 12 - alkyl, C1-C6-alkoxy, hydroxy, nitro and / or halogen mono- or polysubstituted, X is halogen, in particular chlorine or bromine, and n is 0 to 4.
4. The molding composition according to claim 3, wherein the phenylene group, naphthylene group and pyridylene group are unsubstituted.
5. The molding composition according to claim 4, wherein R 1 and R 2 Each is independently an unsubstituted 1,2-phenylene or 1,8-naphthylene, preferably R 1 and R 2 same.
6. The molding composition according to any one of claims 3 to 5, wherein n is 0.
7. The molding composition according to any one of the preceding claims, comprising as component (A) a crystalline polymer material selected from polyamides or blends containing polyamides.
8. The molding composition according to any one of the preceding claims, comprising as component (D) an amorphous polymer material selected from polyamides.
9. The molding composition according to any one of the preceding claims, comprising as component (A) a crystalline polymer material selected from polyamides or blends containing polyamides and as component (D) an amorphous polymer material selected from PA 6I, PA6I / 6T or a combination thereof.
10. The molding composition according to any one of the preceding claims 1 to 6, comprising as component (A) a crystalline polymer material selected from polyesters or polyester-containing blends. 11 . The molding composition according to claim 10 , comprising, as component (A), a polyalkylene terephthalate or a blend comprising a polyalkylene terephthalate.
12. The molding composition according to any one of the preceding claims 10 or 11, comprising as component (D) a combination of a polyester copolymer selected from PETG, PCTG or a combination thereof and polystyrene.
13. The molding composition according to claim 12, comprising as component (D) a combination of polystyrene and PETG.
14. The molding composition according to any one of the preceding claims 10 to 13, comprising as component (A) a polyalkylene terephthalate or a blend containing a polyalkylene terephthalate and as component (D) a combination of polystyrene and PETG.
15. The molding composition according to any one of the preceding claims, wherein the component (E) comprises a nucleating agent, preferably selected from alkali metal carbonates, alkali metal bicarbonates or any combination thereof, more preferably sodium carbonate, sodium bicarbonate or a combination thereof.
16. The molding composition according to any of the preceding claims, wherein the component (B) comprises glass fibers.
17. The molding composition according to any of the preceding claims, wherein component (A) is present in an amount of 30 to 80% by weight, preferably 35 to 75% by weight.
18. The molding composition according to any of the preceding claims, wherein component (B) is present in an amount of 0.03 to 0.3% by weight, preferably 0.04 to 0.2% by weight.
19. The molding composition according to any one of the preceding claims, wherein component (C) is present in an amount of 0.5 to 50% by weight, preferably 10 to 40% by weight, more preferably 20 to 40% by weight.
20. The molding composition according to any one of the preceding claims, wherein component (D) is present in an amount of 1 to 50% by weight, preferably 10 to 40% by weight, more preferably 15 to 35% by weight.
21. The molding composition according to any of the preceding claims, wherein the component (E) is present and comprises a nucleating agent in an amount of 0.01 to 10% by weight, preferably 0.05 to 6% by weight, more preferably 0.1 to 2% by weight or 0.1 to 0.5% by weight, based on the total weight of the molding composition.
22. Use of the molding composition according to any of the preceding claims for producing laser-transparent plastic parts or articles.
23. Article produced using the molding composition according to any one of the preceding claims 1 to 21, for example a housing for an automotive radar or automotive camera.
Citation Information
Patent Citations
Black perylene pigments
WO2005078023A3
Laser-transparent PBT comprising organic additives
WO2011154518A1
Resin composition, kit, method for producing resin composition, method for producing molded article, and molded article
WO2019216368A1